The Antifungal Itraconazole Is a Potent Inhibitor of Chikungunya Virus Replication - Policastro, Lucca R.; Dolci, Isabela; Godoy, Andre S.; Silva Júnior, José V. J.; Ruiz, Uriel E. A.; Santos, Igor A.; Jardim, Ana C. G. [UNESP]; Samby, Kirandeep; Burrows, Jeremy N.; Wells, Timothy N. C.; Gil, Laura H. V. G.; Oliva, Glaucius; et al. (MDPI, 2022)
Chikungunya virus (CHIKV) is the causative agent of chikungunya fever, a disabling disease that can cause long-term severe arthritis. Since the last large CHIKV outbreak in 2015, the reemergence of the virus represents a serious public health concern. The morbidity associated with viral infection emphasizes the need for the development of specific anti-CHIKV drugs. Herein, we describe the development and characterization of a CHIKV reporter replicon cell line and its use in replicon-based screenings. We tested 960 compounds from MMV/DNDi Open Box libraries and identified four candidates with interesting antiviral activities, which were confirmed in viral infection assays employing CHIKV-nanoluc and BHK-21 cells. The most noteworthy compound identified was itraconazole (ITZ), an orally available, safe, and cheap antifungal, that showed high selectivity indexes of >312 and >294 in both replicon-based and viral infection assays, respectively. The antiviral activity of this molecule has been described against positive-sense single stranded RNA viruses (+ssRNA) and was related to cholesterol metabolism that could affect the formation of the replication organelles. Although its precise mechanism of action against CHIKV still needs to be elucidated, our results demonstrate that ITZ is a potent inhibitor of the viral replication that could be repurposed as a broad-spectrum antiviral.
Keywords: antiviral; Chikungunya virus; drug development; Itraconazole; replicon-based assays